Mach number influence on level of flow non-uniformity behind the arrays with gas-dynamic control of blades flow - Терещенко, Юрий Матвеевич; Ластивка, Иван Алексеевич; Дорошенко, Екатерина Викторовна; Волянская, Лариса Георгиевна (Eastern-European Journal of Enterprise Technologies, 2012)
The article concerns the unevenness of airflow behind the array of airfoils of input guide vanes of axialflow compressor of gas-turbine engine at different Mach numbers and at gas-dynamic impact on flow pattern. The impact on the flow, in order to ensure stable flow, elimination or containment of flow separation, increase of stability of the boundary layer, is called the control of flow separation. Active control of compressor arrays flow is performed by gas injection into the boundary layer or by suction of the boundary layer from the surface of the blade. The curve of dependence of the level of flow unevenness α from the intensity of gas-dynamic control of flow structure, characterized by dimensionless coefficient of injection impulse cμ , was derived, on the basis of numerical simulation of flow in array of airfoils with active flow control at different Mach numbers and at different distance x from the exit edge of the airfoil along the axis of the trail. The analysis of the results shows that the change of the Mach numbers affects the efficiency of the gasdynamic control and the level of flow unevenness. In the range of Mach numbers М=0,5–0,9, the level of unevenness of flow behind the arrays of guide vanes at a distance of x =0,1–0,2 behind the exit edge can be reduced to values α =0,005–0,01 at the intensity of control of aerodynamic trails cμ =0,043–0,045.